NARRATIVE REVIEW OF ADJUSTMENT DISORDERS AMONG FRESHMEN - Edward, Sara Nabeel; Amin, Nazar Mohammad Mohammad; Abdulkareem, Makwan (Transpublika Publisher, 2024)
Adjustment disorders refer to the psychological reactions to adapt to new circumstances, including situations such as divorce, major work change, transition from school to university, or migration. This study aimed at summarizing adjustment disorders in a single short paper by using different recent sources and references. This review article was conducted by using deferent recently published articles considering adjustment disorders generally and its occurrence among first year student of colleges specifically. Adjustment disorders are very common mental health issues that arise in response to significant changes in life style and warrant proper assessment and evaluation in order to maximize daily functioning.